Blended Learning in the Teaching of English as a Foreign Language: An Educational Challenge - Carol Anne Ochoa Alpala; Eliana Edith Roberto Flórez (Asociación Colombiana de Profesores de Ingles, 2011)
Blended Learning has become one of the most common ways to teach EFL (English as a Foreign Language) due to its double component, which integrates Face-to-Face classes with virtual learning in order to offer students a wide range of materials and resources organized in a methodological way. Over the years, teachers and students have changed the way this educational process is seen because new technologies have been implemented and teachers have to propose new ways of working to display materials that complement EFL Face-to-Face classes. However, the implementation of a Blended Course must have a pedagogical foundation for each setting where it is planned in order to be developed. This article seeks to present some integrative components of Blended Learning and how they have been applied in several researches done in different contexts as well as to present some considerations to keep in mind when designing, implementing and evaluating this model. Besides, it encourages teachers to reflect upon Blended Learning (BL) as a potential and different way to approach learning EFL, taking advantage of all the emerging pedagogical tools.